Does genetic variability in weeds respond to non‐chemical selection pressure in arable fields?. (7th June 2019) - Darmency, H
Summary: At a time when herbicide use is being challenged by the selection of herbicide‐resistant weeds, reliance on other, innovative weed control strategies is becoming increasingly necessary. However, one may question the sustainability of these novel farming practices if weeds adapt rapidly to these non‐chemical selection pressures. Although farmers and agronomists impose many selective processes through farming practices, there is a paucity of literature demonstrating these selection cases in arable fields. In contrast to the relatively simple case of herbicide resistance, random trait association and variability in selection pressures in field conditions could explain why there are so few clear examples of adaptive processes to non‐chemical control in arable fields.